Survival strategies of rubber farmers in Nagari Batukambing, Ampek Nagari District, Agam Regency, West Sumatra Province, Indonesia - Irwan Irwan; Mustaqim Mustaqim; Felia Siska; Lisa Nurariyanti; Hanifaturrahmi Andrina (Insan Akademika Publications, 2025)
: Agriculture is a crucial sector in the Indonesian economy, especially in rural areas that rely on agricultural activities as a source of livelihood. One important agricultural commodity is rubber, which not only serves as a source of income for farmers but also contributes to both the local and national economy. In Nagari Batukambing, Ampek Nagari District, Agam Regency, West Sumatra Province, rubber farmers play a central role in rubber production, although they often face various economic and social challenges. This study aims to analyze the survival strategies of rubber farmers in Nagari Batukambing, Ampek Nagari District, Agam Regency, West Sumatra Province. The research utilizes the livelihood strategy theory proposed by Ellis, which focuses on the utilization of livelihood assets, including human capital, natural capital, physical capital, financial capital, and social capital. This study adopts a qualitative approach with a descriptive research type. Data collection methods include document study, non-participant observation, and in-depth interviews. Data analysis involves several steps: data collection, data reduction, data presentation, and conclusion drawing. The research findings have significant implications for both farmers and agricultural policy. Farmers are encouraged to prioritize skill development and ongoing education to adapt to changing agricultural practices, while also diversifying their crops to reduce financial risks and enhance food security. Efficient use of tools and equipment should be emphasized to boost productivity, alongside robust financial management through savings and accessible loans to support investments and manage unexpected expenses. Strengthening social networks among farmers and landowners fosters mutual support and collaboration. For policymakers, there is a need to develop support programs that provide training, improve access to microcredit, invest in agricultural infrastructure, and encourage cooperative initiatives to enhance farmers' bargaining power. Overall, these strategies and policies can significantly contribute to the resilience and sustainability of farming communities in Nagari Batukambing.